Vertex-strength of fuzzy graphs - Changiz Eslahchi; B. N. Onagh (International Journal of Mathematics and Mathematical Sciences)
The fuzzy coloring of a fuzzy graph was defined by the authors in Eslahchi and Onagh (2004). In this paper we define the chromatic fuzzy sum and strength of fuzzy graph. Some properties of these concepts are studied. It is shown that there exists an upper (a lower) bound for the chromatic fuzzy sum of a fuzzy graph.